(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The role of assessment in the education of English Language Learners (ELLs) and emergent bilinguals is crucial in monitoring their language acquisition and providing targeted support. This thesis explores various methods and tools used to assess the language proficiency of non-native English speakers, highlighting their importance in the educational process. Three primary purposes of language assessments are outlined: administrative, instructional, and research-based.